Metabolomic profiling of indigenous lactic acid bacteria reveals functional traits shaping the flavor and bioactivity of Ecuadorian coffee - Cifuentes, Victor; Marinas, Ioana C.; Marinescu, George Cătălin; Popescu, Roua Gabriela; Chifiriuc, Mariana C.; Tenea, Gabriela N. (Frontiers in Microbiology, 2025)
IntroductionMicrobial fermentation by lactic acid bacteria (LAB) significantly influences the flavor, quality, and functional attributes of coffee. However, the specific metabolic outputs and roles of LAB native strains to distinct Coffea arabica ecosystems remain insufficiently understood. This study aimed to characterize the metabolite profiles and functional signatures of cell-free supernatants (CFS) from six indigenous LAB strains isolated from three Ecuadorian coffee varieties, C. arabica var. Typica (TYP), C. arabica var. Yellow Caturra (CATY), and C. arabica var. Red Caturra (CATR), harvested at two ripening stages (green and yellow/red).MethodsMetabolite profiling was performed using capillary liquid chromatography tandem mass spectrometry (LC-MS/MS) with a SWATH-based data-independent acquisition (DIA) strategy in positive electrospray ionization (ESI+) mode, enabling detection of metabolites associated with flavor development, stress response, and antimicrobial potential. Functional group analysis via attenuated total reflectance Fourier transforms infrared (ATR-FTIR) spectroscopy provided insights into structural and biochemical changes, including protein, carbohydrate, and lipid modifications during LAB activity. Total polyphenol content (TPC) and total flavonoid content (TFC) were quantified to assess nutritional and antioxidant shifts.ResultsStrain-specific metabolic signatures were identified. Lactiplantibacillus strains (B3, B6, B9, B10, B17) showed enriched biosynthesis of harmala alkaloids, isoflavonoids, indole derivatives, and bioactive peptides (e.g., FruLeuIle), which may contribute to enhanced aroma and bioactivity. Weissella (B19) exhibited a simpler profile, dominated by organic acids and benzene derivatives, potentially enhancing acidity and freshness. FTIR analysis revealed that B6, B10, B17, and B19 released distinctive extracellular polysaccharides, proteins, and aromatic compounds, shaping the fermented matrix.ConclusionThis study demonstrates the functional diversity of indigenous LAB strains from C. arabica cherries, showing that their strain-specific metabolic signatures reshape the fermentation matrix and highlighting their potential for targeted microbial selection to enhance flavor complexity, quality, and the market value of Ecuadorian specialty coffees.